Numerical model of noise effect in full field data - Syed Muhammad, Kashif (IIUM Press, 2011)
This chapter discusses the important issue of experimental noise simulation in the formulation of piecewise virtual fields method for the characterization of thin composite plate. In actual practice, the full field data captured through an optical dive on the surface of a specimen is always prone to some noise effect. In order to accurately identify eth unknown rigidities it is necessary to cancel the noise effect. The present chapter discuss about the methodology and numerical model that caters for the noise effect and its removal to get an unbiased identification.